Developing the Hungarian version of the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) - István Somoskövi; Andrea Radácsi; Ákos Károly Nagy; Márta Radnai (Hungarian Dental Association, 2018)
Introduction: Temporomandibular disorders (TMDs) are among the most challenging group of diseases in medicine regarding both their etiology and therapy. The diagnosis of TMD has evolved significantly over the last decades. The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) was introduced in 2014 by Schiffman et al. The aim of the developers was to create a standardized diagnostic tool intended for use in both clinical and research settings. The DC/TMD has been translated to several languages. The aim of our research team was to develop the Hungarian version. Materials and methods: Translation and cultural adaptation of DC/TMD is a multistep process that follows the guidelines set up by the International Network for Orofacial Pain and Related Disorders Methodology in order to ensure that the different language versions created are equally useable as the original one. Results: We started developing the Hungarian version of DC/TMD in 2015 and finalized the translation phase in 2017. After making it available to others, we are planning to start testing the instrument in the Hungarian population. Discussion: The translation process has been a unique experience for our team which had to face several difficulties during the development. In this article we discuss the process of translation and cultural adaptation. We believe that professionals who work in this field of dentistry can benefit from getting acquainted with the DC/TMD and its benefits in TMD diagnostics.